The Effectiveness of Hyperbaric Oxygen Therapy in Acute Acoustic Trauma: A Narrative Review of Clinical Evidence and Treatment Considerations - Bukwald, Weronika; Muzyka, Natalia; Rumin, Magdalena; Abramowicz, Amanda; Panek, Gabriela; Piliński, Remigiusz; Prusek, Adam; Gosztyła, Dominika; Giersz, Jakub; Kość, Kacper (Journal of Education, Health and Sport, 2026)
Background Acute acoustic trauma (AAT) is a form of sensorineural hearing loss caused by exposure to sudden and intense noise. This condition results in mechanical damage to cochlear hair cells. It also leads to disturbances in cochlear microcirculation and tissue hypoxia. Due to the risk of permanent hearing impairment, rapid and effective treatment is essential. The aim of this review was to evaluate current therapeutic methods in AAT and to assess the potential role of hyperbaric oxygen therapy (HBOT) as an adjunctive treatment. Methods A literature search was conducted using PubMed and Google Scholar to identify studies evaluating the role of HBOT in the management of acute acoustic trauma. Both clinical and experimental studies were considered for background context, while the analysis focused primarily on clinical evidence. Relevant full-text articles were analyzed. The analysis focused on treatment protocols, timing of therapy initiation, and reported clinical outcomes. Results The rationale for HBOT in AAT is its ability to increase tissue oxygenation and counteract cochlear hypoxia resulting from microcirculatory disturbances following acoustic injury. Improved oxygen delivery may support cellular metabolism and limit secondary inflammatory processes. It may also reduce permanent hair cell damage. Available clinical studies suggest that HBOT may improve hearing outcomes, especially when administered early after injury and in combination with systemic corticosteroid therapy. Conclusions Current clinical evidence indicates that HBOT may represent a beneficial adjunctive therapy in the management of acute acoustic trauma. However, the methodological quality of available studies remains limited. Well-designed prospective randomized trials with standardized treatment protocols are needed. These studies should help define the optimal therapeutic strategy and the most effective therapeutic window for HBOT in AAT.